The Circular Chromatic Index of Flower Snarks - Ghebleh, Mohammad; Král', Daniel; Norine, Serguei; Thomas, Robin (The Electronic Journal of Combinatorics, 2006)
We determine the circular chromatic index of flower snarks, by showing that $χ'_c(F_{3})=7/2$, $χ'_c(F_{5})=17/5$ and $χ'_c(F_{k})=10/3$ for every odd integer $k\ge 7$, where $F_k$ denotes the flower snark on $4k$ vertices.